Performing Anticoagulation: A Puzzling Case of Cholesterol Embolization Syndrome. Issue 10 (27th January 2017) - Igarashi, Yusuke; Akimoto, Tetsu; Kobayashi, Takahisa; Iwazu, Yoshitaka; Miki, Takuya; Otani-Takei, Naoko; Imai, Toshimi; Sugase, Taro; Masuda, Takahiro; Takeda, Shin-ichi; Muto, Shigeaki; Nagata, Daisuke
The avoidance of any form of anticoagulation is advised in cases of cholesterol embolization syndrome (CES). We herein describe a case of CES in a man with a history of unprovoked pulmonary embolism for which warfarinization was performed. Despite anecdotal reports of successful anticoagulation in CES patients with certain indications, irreversible renal failure, which was sufficiently severe to require chronic hemodialysis, eventually developed in our patient. Our results emphasize the pitfalls of this procedure, which imply its limited feasibility and safety. Several therapeutic concerns associated with this case are also discussed.